Functional Analysis of Dynactin and Cytoplasmic Dynein in Slow Axonal Transport - Dillman III, James F. (J Neurosci, 1996)
The neuron moves protein and membrane from the cell body to the synapse and back via fast and slow axonal transport. Little is known about the mechanism of microtubule movement in slow axonal transport, although cytoplasmic dynein, the motor for retrograde fast axonal transport of membranous organelles, has been proposed to also slide microtubules down the axon. We previously showed that most of the cytoplasmic dynein moving in the anterograde direction in the axon is associated with the microfilaments and other proteins of the slow component b (SCb) transport complex. The dynactin complex binds dynein, and it has been suggested that dynactin also associates with microfilaments. We therefore examined the role of dynein and dynactin in slow axonal transport. We find that most of the dynactin is also transported in SCb, including dynactin, which contains the neuron-specific splice variant p135(Glued), which binds dynein but not microtubules. Furthermore, SCb dynein binds dynactin in vitro. SCb dynein, like dynein from brain, binds microtubules in an ATP-sensitive manner, whereas brain dynactin binds microtubules in a salt-dependent manner. Dynactin from SCb does not bind microtubules, indicating that the binding of dynactin to microtubules is regulated and suggesting that the role of SCb dynactin is to bind dynein, not microtubules. These data support a model in which dynactin links the cytoplasmic dynein to the SCb transport complex. Dynein then may interact transiently with microtubules to slide them down the axon at the slower rate of SCa.